2019
DOI: 10.1111/sapm.12285
|View full text |Cite
|
Sign up to set email alerts
|

Construction of solutions of the defocusing nonlinear Schrödinger equation with asymptotically time‐periodic boundary values

Abstract: We study the defocusing nonlinear Schrödinger equation in the quarter plane with asymptotically periodic boundary values. We use the unified transform method, also known as the Fokas method, and the Deift‐Zhou nonlinear steepest descent method to construct solutions in a sector close to the boundary whose leading behavior is described by a single exponential plane wave. Furthermore, we compute the subleading terms in the long‐time asymptotics of the constructed solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…The proof of Lemma 5.3 does not rely on an explicit expression of r 2 on (E 1 , E 2 ) in order to construct a function r 2,a with the desired properties. This generalizes a related construction in [25], where r 2 was defined on (E 1 , E 2 ) in terms of r by r 2 (k) := −r(k)/(1+r(k 2 )). For consistency, additional assumptions were made in [25], namely that r = ±i on (E 1 , E 2 ) and r(E j ) ∈ {±i}, j = 1, 2.…”
Section: Lemma 52 (Analytic Approximation Of R)mentioning
confidence: 63%
See 4 more Smart Citations
“…The proof of Lemma 5.3 does not rely on an explicit expression of r 2 on (E 1 , E 2 ) in order to construct a function r 2,a with the desired properties. This generalizes a related construction in [25], where r 2 was defined on (E 1 , E 2 ) in terms of r by r 2 (k) := −r(k)/(1+r(k 2 )). For consistency, additional assumptions were made in [25], namely that r = ±i on (E 1 , E 2 ) and r(E j ) ∈ {±i}, j = 1, 2.…”
Section: Lemma 52 (Analytic Approximation Of R)mentioning
confidence: 63%
“…This generalizes a related construction in [25], where r 2 was defined on (E 1 , E 2 ) in terms of r by r 2 (k) := −r(k)/(1+r(k 2 )). For consistency, additional assumptions were made in [25], namely that r = ±i on (E 1 , E 2 ) and r(E j ) ∈ {±i}, j = 1, 2. However, numerical experiments have shown that these assumptions are not satisfied in general.…”
Section: Lemma 52 (Analytic Approximation Of R)mentioning
confidence: 63%
See 3 more Smart Citations